The Contribution of Self-Directed Learning to Arabic Language Materials to the Improvement of Students' Writing Literacy - Mukmin, Mukmin; Hidayah, Nurul; Yusuf, Muhammad; Siska, Siska (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
Arabic language learning in schools often faces challenges in motivating students to be active and independent in learning. Therefore, the SDL approach is expected to improve students' Arabic language skills and suit their needs and learning styles. This study aims to examine the effectiveness of students' writing literacy in Arabic language materials with the self-directed learning (SDL) approach. This research uses a mixed method with sequential explanatory type, which combines quantitative and qualitative data. The results of this study revealed that the improvement of students' writing skills and mastery of Islamic learning had a positive impact on their academic ability and religious understanding, while supporting the balanced development of intellectual and spiritual skills. Through this approach, students are not only more courageous in expressing themselves using Arabic, but also feel happier because learning is tailored to their individual abilities and learning styles. The impact of this study shows that the SDL approach can be an effective solution to improve students' motivation and Arabic language competence, and can be applied in other madrasahs to support more enjoyable and effective learning.